Website Ilmu Faraid Disertai Contoh Kasus - Hutoro, Kirko; , Husni Thamrin, S.T, M.T, Ph.D (2016)
Islamic inheritance jurisprudence is a science in the teaching of Islam that studies of inheritance in accordance Shari'ah Prophet that have been submitted through the Qur'an and the Sunnah of the Prophet and the consensus of the Companions and scholars. Often the problem of inheritance to be the cause of family breakdown because family members do not understand on the rules and provisions of Islamic inheritance law. Along with the development of technology and information, the Internet-based learning into an alternative learning media to convey knowledge. The purpose of making these Islamic inheritance jurisprudence website is to help people, especially Muslims in learning about inheritance appropriate Islamic shar'iah. Design of the Islamic inheritance jurisprudence website is using UML, use-case diagrams and activity diagrams are used to describe the graphical diagrams. This website is designed use PHP and MYSQL database. Islamic inheritance jurisprudence resource materials obtained from books "Seri Fiqih Kehidupan [15] : Mawaris". Case search material obtained from application "i-waris" is released by Mosque Raya Al-Azhar East Jakarta. The results provided by this website is about the Islamic inheritance jurisprudence and case search.